Rethinking Legal Validity and Contractual Structures of Shariah-Compliant Credit Cards: A Study on DSN-MUI Fatwa - Alfarisi, Muhammad Adib; Suhedi, Suhedi; Ezzerouali, Souad Ahmed; Andrianti, Dyah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The rapid evolution of Islamic financial products has raised critical questions about the legal validity and practical enforceability of Sharia credit cards within Indonesia’s dual legal system. This study seeks to rethink the legal validity of Sharia credit cards by moving beyond the fiqh-based legitimacy of Fatwa No. 54/DSN-MUI/X/2006 to examine their implementation under Indonesia’s positive law, regulatory oversight, and the objectives of maqāṣid al-sharī‘ah. Employing a qualitative legal content analysis, the research identifies six potentially relevant contracts kafālah, wakālah, ḥawālah, murābaḥah, qardh, and ijārah and critically assesses why the DSN-MUI ultimately operationalized only three: qardh, kafālah, and ijārah. The study argues that this tri-contract structure provides normative coherence but remains legally contingent on its harmonization with the Otoritas Jasa Keuangan (OJK) and Bank Indonesia (BI) regulations governing multi-contract products. Findings reveal that while the fatwa aligns with maqāṣid al-sharī‘ah protecting wealth (ḥifẓ al-māl) and promoting justice (‘adl) by eliminating riba its enforceability under civil contract law, particularly regarding ta‘wīḍ (compensation) and gharāmah (late penalty), remains ambiguous. Comparative insights from Malaysia and the Middle East underscore the need for a regulatory framework that integrates fatwa-based legality within codified financial law. Consequently, this “rethinking” offers a new analytical framework normative, structural, and positive legal validity to bridge the gap between Sharī‘ah doctrine and enforceable Islamic financial governance in Indonesia.